Penerapan Buy Back Guarantee Bagi Pembeli dan Developer Berdasarkan Undang-Undang Perlindungan Konsumen - Milentina, Dinar Intan; Abadi, Suwarno (Universitas Wijaya Putra, 2023)
Housing is one of the needs that must be met by all people in the world, both in developing and developed countries, in addition to food needs, proper housing certainly influences the formation of the nation's personality so that they can socialize well in society. Every year the need for houses as a place to live or occupancy is increasing due to the increasing population both in rural and urban areas. Basically, fulfilling housing needs is the responsibility of each community itself, but the state helps the community to obtain and provides convenience in obtaining housing through housing developers. Housing developers or developers who have built their homes can sell to debtors with a gradual cash payment system and Home Ownership Credit (KPR), a gradual cash payment system. For KPR, a credit agreement can be signed which contains the approved credit value and the credit loan repayment period. The credit agreement made must be known by the housing developer or developer, which can be in the form of a private deed, or a deed drawn up before a notary or land deed official.